2016
DOI: 10.3389/fphar.2015.00321
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal Kinase (JNK) Signaling as a Therapeutic Target for Alzheimer’s Disease

Abstract: c-Jun N-terminal kinases (JNKs) are a family of protein kinases that play a central role in stress signaling pathways implicated in gene expression, neuronal plasticity, regeneration, cell death, and regulation of cellular senescence. It has been shown that there is a JNK pathway activation after exposure to different stressing factors, including cytokines, growth factors, oxidative stress, unfolded protein response signals or Aβ peptides. Altogether, JNKs have become a focus of screening strategies searching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
245
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(257 citation statements)
references
References 114 publications
(131 reference statements)
9
245
0
3
Order By: Relevance
“…In addition, results of studies in vitro and in vivo show that alterations of JNK pathways are associated with pathogenesis and apoptosis of neurons in AD [31]. Importantly, evidence shows that pretreatment with the JNK inhibitor SP600125 prior to Aβ 25–35 exposure blocked expression of Bcl-2 family members, including Bcl-w and Bim [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, results of studies in vitro and in vivo show that alterations of JNK pathways are associated with pathogenesis and apoptosis of neurons in AD [31]. Importantly, evidence shows that pretreatment with the JNK inhibitor SP600125 prior to Aβ 25–35 exposure blocked expression of Bcl-2 family members, including Bcl-w and Bim [21].…”
Section: Discussionmentioning
confidence: 99%
“…By carefully studying the time-dependent changes in enzyme activities, mitochondrial permeability and histological features in the absence or presence of specific JNK inhibitors, it was concluded that translocation of activated p-JNK to mitochondria and subsequent phosphorylation of many mitochondrial proteins are critically important in promoting mitochondrial dysfunction, mitochondrial permeability change and necrotic tissue injury usually observed at later time points (Jang et al, 2015). Similarly, phosphorylation of many proteins such as Tau (Wang et al, 2013) and Bax in neuronal tissues can produce neurofibrillary tangles (NFTs) and apoptosis of neuronal cells, respectively, contributing to neurodegeneration (Byun et al, 2012; Byun et al, 2014; Yarza et al, 2016). However, the number and identity of the neuronal proteins, that can be phosphorylated by activated p-JNK, p-p38K, and/or GSK3β in brains (Forlenza et al, 2011; Jimenez et al, 2011; Jo et al, 2011), need to be investigated to further delineate the causal role of protein phosphorylation in promoting neurodegenerative diseases.…”
Section: Consequences Of Increased Nitroxidative Stressmentioning
confidence: 99%
“…MUC1-silenced MOLM-14 and THP-1 cells were assessed for their expression of ERK and JNK; described mediators of c-Jun transcription 3941 and phosphorylation, 42,43 respectively. MUC1 silencing resulted in increased levels of total and phosphorylated ERK and JNK as demonstrated by immunoblot analysis (Figures 4g and h; n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, given the marked increase in phospho c-Jun expression following MUC1 silencing, we sought to examine whether MUC1 signaling also effects c-Jun activation. Indeed, analysis of JNK expression, which has been widely shown to effect c-Jun activation, 42,43 was demonstrated to be significantly increased following MUC1 silencing in both MOLM-14 and THP-1 cells. These results are consistent with reported JNK regulation by MUC1 signaling.…”
Section: Discussionmentioning
confidence: 99%